Why Institutional Environments for Agroforestry Seed Systems Matter - CGIAR Research Program on Forests, Trees and Agroforestry (2018)
Analysis of reasons for and suggestions of measures to mitigate the lack of adoption of efficient germplasm delivery in productive systems and for landscape restoration.